A hollow spherical Fe, N co-doped porous carbon-based catalyst and its preparation method and application
By using polystyrene ball templates to prepare hollow spherical Fe and N co-doped carbon-based catalysts, the problems of low oxygen reduction reaction efficiency and poor catalyst stability of zinc air batteries are solved, and efficient and environmentally friendly zinc air batteries are achieved.
Patent Information
- Application Number
- CN202210827879.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-13
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2042-07-13
AI Technical Summary
The kinetic process of the oxygen reduction reaction of zinc air batteries is slow during discharge, which affects the energy conversion efficiency of the battery. Traditional precious metal catalysts are scarce, have high costs and poor stability, and the synthesis of hollow structure catalysts is complex and environmentally friendly.
Polystyrene spheres are used as hard templates to prepare Fe and N co-doped carbon-based catalysts through in-situ oxidation polymerization to form hollow spherical structures, simplifying the synthesis process and using PS spheres to decompose gas pores to improve the active site of the catalyst Exposure and material transfer efficiency.
It improves the oxygen reduction reaction rate and battery performance, reduces the overpotential of the oxygen reduction reaction, enhances the stability and environmental protection of the catalyst, realizes efficient zinc-air battery application, and is simple and easy to operate.
Smart Images

Figure CN115224291B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalyst synthesis technology and energy conversion device technology, relates to the preparation of zinc-air battery catalysts, and specifically relates to a hollow spherical Fe, N co-doped carbon-based high-efficiency zinc-air battery catalyst and a preparation method and application thereof. Background Art
[0002] In the past few decades, the application of electrochemical energy storage and conversion systems has alleviated the demand and consumption of traditional fossil fuels. Compared with traditional lead-acid, nickel-cadmium and lithium-ion batteries, zinc-air batteries not only have a higher theoretical energy density (1086Wh kg -1 ), and also has the advantages of high safety, low cost, and good stability. During the operation of the zinc-air battery, the cathode only needs to continuously consume oxygen in the air without consuming other substances. The metal zinc used as the anode is abundant in resources, relatively stable in an open system, and does not have serious safety hazards. Therefore, the zinc-air battery has a good development and application prospect, and it is considered to be one of the most promising energy conversion devices for the new generation of portable electronic devices.
[0003] However, during the discharge process of zinc-air batteries, the kinetics of the oxygen reduction reaction (ORR) on the air electrode is slow, which seriously affects the energy conversion efficiency of the battery. Efficient oxygen electrocatalysts must be used to reduce the activation energy of the electrode reaction and improve the energy conversion efficiency, output power and specific capacity. It is well known that traditional precious metal catalysts such as platinum and ruthenium have high catalytic activity, but they have the disadvantages of scarce resources, high cost and poor stability; this hinders large-scale application in the future.
[0004] Among them, the composite catalyst obtained by combining transition metal compound nanostructures with hybrid carbon materials has become one of the research hotspots in recent years. This is because:
[0005] 1) This type of catalyst has a rich pore structure and a large specific surface area, which helps to improve the mass transfer efficiency of the catalytic reaction.
[0006] 2) Metal nanoparticles and heteroatom-doped carbon substrates provide abundant active sites for oxygen release and oxygen adsorption, respectively.
[0007] 3) The good conductivity of the carbon substrate significantly improves the charge transfer efficiency of the composite catalyst.
[0008] 4) The synergistic interface between heterogeneous materials through close contact can significantly improve the stability of catalysts and prevent nanoagglomeration.
[0009] 5) The ORR catalytic performance of the hybrid carbon substrate can be further improved by bonding metal nanoparticles with hybrid carbon at the synergistic interface. These advantages endow this type of catalyst with efficient ORR activity and stability, making it very suitable for use as an air electrode catalyst in metal-air batteries.
[0010] However, MNCs usually face problems such as unstable catalytic performance and poor experimental reproducibility due to agglomeration and inhomogeneity (New J. Chem. 45 (2021) 5421~5427). 3+ , achieving Fe 3+ The in-situ oxidative polymerization of the polymer monomer was initiated to uniformly coat the metal (iron, zinc)-polypyrrole on the surface of the PS sphere, and then a hollow spherical Fe-NC catalyst was obtained by further high-temperature pyrolysis.
[0011] In addition, for the ORR process occurring at the interface, it is very important to expose more active sites and improve the utilization of the active sites on the outer surface. In the electrocatalytic reaction process occurring at the electrode / electrolyte interface, the morphology control of carbon-based electrocatalysts plays a key role in improving mass transfer, surface area and pore utilization. Therefore, it is crucial to rationally design the structure of the ORR catalyst. The catalytic active sites are dispersed on the curved surface (i.e., nanospheres). The construction of a hollow sphere structure can not only expose more active sites, but also promote the material transport in the ORR, thereby increasing the ORR rate. The change in its radius of curvature can not only provide more available surface area, but also adjust the microenvironment of the active site, such as heteroatom doping (Journal of the American Chemical Society, 2020, 142(5): 2404-2412.), defect generation (Nanoscale, 2021, 13(31): 13249-13255.), and changes in the coordination environment (Small, 2022, 18(2): 2105387.), thereby improving the ORR performance by reducing the O2 adsorption energy. However, the synthesis of hollow structure catalysts usually involves the use of complex hard template methods, such as silica colloids and ordered mesoporous silica (Nano Energy, 2017, 40: 462-470.; Journal of Materials Chemistry A, 2017, 5(13): 6025-6031.). Moreover, the inert SiO2 template needs to be removed under harsh operating conditions (e.g., HF solution in these studies), which inevitably etches away most of the micropore-supported MN near the outer surface of the electrocatalyst. x( Carbon, 2016, 99:514-522.).
[0012] In view of this, in order to improve the synthesis efficiency and environmental protection, it is very important to choose a suitable template. According to the characteristics of the pyrolysis method for preparing MNC, the present invention cleverly selects PS balls as hard templates to control the morphology at low temperatures, and is removed during the high-temperature pyrolysis process to prepare the catalyst (PS balls decompose / volatize at 340-430°C, Advanced Functional Materials, 2018, 28(2): 1704208.). It is worth mentioning that the gas products of the decomposition of the PS ball hard template can also achieve the effect of pore formation. Summary of the invention
[0013] In view of the above technical problems, the present invention proposes a hollow spherical Fe, N co-doped carbon-based high-efficiency zinc-air battery catalyst and its preparation method and application, and constructs a hollow nano-spherical Fe-NC catalyst. The unique morphology can not only expose more active sites, but also promote the material transport in ORR, thereby increasing the ORR rate and thus improving the ORR performance. The use of a pyrolyzable template simplifies the steps of the traditional hard template synthesis method, and the decomposed gas product can also achieve the effect of pore formation.
[0014] In order to solve the above technical problems, the present invention adopts the following technical scheme: the present invention uses polystyrene as a template, iron salt, zinc salt and nitrogen-containing heteroatom polymer monomer as raw materials, obtains a polymer layer of chelated Fe atoms coated on the surface of polystyrene balls by in-situ oxidative polymerization, and obtains a hollow spherical Fe, N co-doped porous carbon (Fe-N-HPCs)-based high-efficiency zinc-air battery catalyst by calcination and acid washing, which specifically includes the following steps:
[0015] (1) Use NaOH solution to extract and remove the inhibitor in the styrene monomer, and add it together with polyvinyl pyrrolidone (PVP) into deionized water, stir evenly, and then introduce N2;
[0016] (2) placing the solution obtained in step (1) in a water bath, heating and stirring, then adding potassium persulfate, and continuing heating and stirring to react;
[0017] (3) After the reaction in step (2) is completed, filtering and drying are performed to obtain powdered polystyrene spheres (PS spheres);
[0018] (4) dissolving the powdered polystyrene spheres and metal salt obtained in step (3) in deionized water, stirring and dissolving, and then ultrasonically dispersing the mixture, which is referred to as solution A; precooling the polymer monomer in an ice water bath, which is referred to as solution B; and then slowly dropping solution A into solution B;
[0019] (5) After the step (4) is completed, the mixture is stirred and evaporated to dryness under water bath conditions, and the resulting powder is collected and carbonized in an Ar / H2 atmosphere to obtain a catalyst precursor;
[0020] (6) The catalyst precursor obtained in step (5) is added to an acid solution, stirred at a constant temperature, and centrifuged and washed until the sample supernatant is neutral, and then the centrifugal substrate is collected and dried to obtain a hollow spherical Fe, N co-doped porous carbon-based catalyst.
[0021] Furthermore, in the step (1), the amount of styrene monomer added is 0.1-0.9 mL, the amount of polyvinyl pyrrolidone PVP added is 0.01-0.05 g, the volume of deionized water is 1-10 mL, and the time of passing N2 is 5-30 minutes.
[0022] In step (2), the heating temperature is 30-85°C, preferably 55-70°C, the heating time is 0.5-3h, and the continuous heating and stirring reaction time is 6-48h.
[0023] Further, the typical preparation method of powdered polystyrene spheres (PS spheres) is as follows:
[0024] Take 0.1-0.9 mL of styrene monomer, use NaOH solution to extract and remove the inhibitor, then add 0.01-0.05 g PVP and 1-10 mL deionized water, and pass N2 into the solution for 5-30 minutes; place the above solution in a water bath and heat at 30-85℃ for 0.5-3h, then add 0.02-0.1g of potassium persulfate, continue heating and stirring for 6-48h; after the reaction is completed, filter and dry to obtain powdered PS balls.
[0025] Furthermore, in step (4), the metal salt is a mixture of an iron salt and a zinc salt, and the mass ratio of the iron salt, the zinc salt and the polystyrene balls is (0.1-0.5):(0.05-0.2):(0.01-0.05), wherein the iron salt includes iron sulfate, iron nitrate or iron chloride, and the zinc salt includes zinc sulfate, zinc nitrate or zinc chloride.
[0026] Furthermore, in step (4), the polymer monomer includes any one of pyrrole, aniline or thiophene, Fe 3+ The molar ratio to the polymer monomer is 1:(0.2~2), and the droplet acceleration rate is 0.05~0.5 mL / min.
[0027] Furthermore, the temperature for stirring and evaporating to dryness in step (5) is 35-85°C.
[0028] Furthermore, in step (5), the volume content of H2 in the Ar / H2 mixed gas is 5%-10%, the carbonization temperature is 700-950°C, the carbonization time is 1-3h, and the heating rate is 3-15°C / min.
[0029] Furthermore, in step (6), the acid solution is a 0.05-2 mol / L dilute sulfuric acid solution, the pickling time is 2-18 h, the stirring temperature is 40-70° C., the drying temperature is 60° C., and the drying time is 8-12 h.
[0030] The hollow spherical Fe and N co-doped porous carbon-based catalyst prepared by the preparation method is uniformly coated on the surface of polystyrene by a chelated bimetallic polymer obtained by in-situ oxidative polymerization.
[0031] The present invention also provides application of the hollow spherical Fe and N co-doped porous carbon-based catalyst in a zinc-air battery.
[0032] The present invention has the following beneficial effects:
[0033] 1. The present invention uses negatively charged polystyrene balls to pre-absorb Fe 3+ , achieving Fe 3+ Initiate in-situ oxidative polymerization of polymer monomers, uniformly coat metal (iron, zinc)-polypyrrole on the surface of PS spheres, and further pyrolyze at high temperature to obtain porous hollow spherical Fe-NC (Fe-N-HPCSs) catalysts. This solves the problems of unstable catalytic performance, poor experimental reproducibility due to material agglomeration or uneven distribution of MNC catalysts prepared by traditional pyrolysis methods.
[0034] 2. The hollow sphere structure designed and constructed by the present invention can not only expose more active sites, but also promote the material transport in ORR, thereby increasing the ORR rate. The change in the radius of curvature can not only provide more available surface area, but also adjust the microenvironment of the active site, thereby improving the ORR performance by reducing the O2 adsorption energy.
[0035] 3. The present invention selects PS spheres as hard templates to control the morphology at low temperature, but is removed during the high-temperature pyrolysis process to prepare the catalyst (PS spheres decompose / volatize at 340-430°C). Moreover, the gas products of the decomposition of the PS sphere hard template can also achieve the effect of pore formation, simplifying the steps of the traditional hard template synthesis method.
[0036] 4. The preparation method of the present invention requires simple equipment, is easy to operate, and has excellent electrocatalytic performance.
[0037] 5. The half-wave potential of the Fe-N-HPCSs catalyst prepared by the present invention in 0.1 mol / L KOH solution is 0.896 V, which exceeds the half-wave potential of 0.843 V of the commercial Pt / C-20% catalyst under the same conditions, greatly reducing the overpotential of the oxygen reduction reaction. Its ORR process conforms to the 4-electron catalytic mechanism and is an ideal oxygen reduction reaction (ORR) catalyst.
[0038] 6. The Fe-N-HPCSs catalyst prepared by the present invention has higher open circuit voltage, stability and power density in zinc-air batteries than commercial Pt / C-20%. It has a power density of 164.13 mW cm -2 The peak power density is three times higher than that of Pt-C-20% and the durability is excellent for 370 h. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0040] Figure 1 This is the XRD pattern of the Fe-N-HPCSs catalyst prepared in Example 3 of the present invention.
[0041] Figure 2 Field emission scanning electron microscopy image of the Fe-N-HPCSs catalyst prepared in Example 3 of the present invention ( Figure 2 a) TEM image ( Figure 2 bc) and electron diffraction patterns ( Figure 2 d).
[0042] Figure 3 N2- adsorption-desorption curve of Fe-N-HPCSs catalyst prepared in Example 3 of the present invention ( Figure 3 a) and pore size distribution curve ( Figure 3 b).
[0043] Figure 4 The XPS spectrum of the Fe-N-HPCSs catalyst prepared in Example 3 of the present invention ( Figure 4 a) N1s high resolution spectrum ( Figure 4 b) Fe2p high resolution spectrum ( Figure 4 c).
[0044] Figure 5 The NC, Fe-NC, Fe-N-HPCSs catalysts prepared in Example 3 of the present invention and commercial Pt-C-20% were in an O2-saturated 0.1 mol / L KOH electrolyte at a scan rate of 10 mV s -1 , LSV curve obtained at a speed of 1600rpm ( Figure 5 a) and Tafel curve ( Figure 5 b).
[0045] Figure 6The ORR-LSV curves of the Fe-N-HPCSs catalyst prepared in Example 3 of the present invention at different rotation speeds ( Figure 6 a), KL equation and electron transfer number ( Figure 6 b). Comparison of ORR cycle stability of Fe-N-HPCSs catalyst and commercial Pt-C-20% ( Figure 6 c).
[0046] Figure 7 Polarization curves and corresponding discharge power density curves of the zinc-air battery assembled with the Fe-N-HPCSs catalyst prepared in Example 3 of the present invention and commercial Pt-C-20% ( Figure 7 a) Open circuit voltage curve comparison chart ( Figure 7 b) Full discharge comparison chart (specific capacity is based on the mass of the zinc negative electrode consumed, Figure 7 c) Rate performance ( Figure 7 d) and a current density of 3 mA cm -2 Lower cycle stability and comparison chart ( Figure 7 e). DETAILED DESCRIPTION
[0047] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] Example 1
[0049] The preparation method of the hollow spherical Fe, N co-doped porous carbon-based high-efficiency zinc-air battery catalyst of this embodiment comprises the following steps:
[0050] (1) Take 0.1 mL of styrene monomer, extract it with NaOH solution to remove the inhibitor, then add 0.02 g of polyvinyl pyrrolidone (PVP) and 5 mL of deionized water, and pass N2 through the solution for 20 minutes;
[0051] (2) Heat the above solution in a water bath at 55°C for 0.5 h, then add 0.05 g of potassium persulfate and continue heating and stirring for 6 h.
[0052] (3) After the reaction is completed, filter and dry to obtain powdered PS balls;
[0053] (4) The powdered polystyrene (PS) spheres obtained in step (3) are dissolved in deionized water with ferric chloride and zinc sulfate, wherein the masses of ferric chloride, zinc sulfate and PS spheres are 0.1 g, 0.08 g and 0.01 g, respectively, and the solution is ultrasonically dispersed and recorded as solution A; 0.2 mmol of pyrrole monomer is precooled in an ice water bath and recorded as solution B; then solution A is slowly added dropwise to solution B at a drop rate of 0.1 mL / min;
[0054] (5) After the addition of step (4) is completed, place the mixture in a constant temperature water bath at 65°C, stir and evaporate to dryness, collect the resulting powder and transfer it to a tube furnace, and carbonize it in an Ar / H2 atmosphere to obtain a precursor. The carbonization temperature is 800°C, the volume content of H2 in the Ar / H2 mixed gas is 8%, the heating rate is 5°C / min, and the carbonization time is 2h;
[0055] (6) The precursor obtained in step (5) is added to a 2 mol / L dilute sulfuric acid solution and placed in a constant temperature water bath at 40°C with stirring, acid-washed for 1 h, and centrifuged until the sample supernatant is neutral. The centrifuged substrate is collected and dried in a vacuum drying oven at 60°C for 8 h to obtain a hollow spherical Fe, N co-doped carbon-based high-efficiency zinc-air battery catalyst.
[0056] Example 2
[0057] The preparation method of the hollow spherical Fe, N co-doped porous carbon-based high-efficiency zinc-air battery catalyst of this embodiment comprises the following steps:
[0058] (1) Take 0.25 mL of styrene monomer, extract it with NaOH solution to remove the inhibitor, then add 0.03 g of PVP and 10 mL of deionized water, and pass N2 through the solution for 15 minutes.
[0059] (2) Heat the above solution in a water bath at 70°C for 2 h. Add 0.03 g of potassium persulfate and continue heating and stirring for 12 h.
[0060] (3) After the reaction is completed, filter and dry to obtain powdered PS balls.
[0061] (4) Mix the powdered PS spheres obtained in step (3) with metal salts. The masses of iron sulfate, zinc nitrate and PS spheres are 0.2 g, 0.1 g and 0.02 g respectively. After stirring and dissolving, ultrasonic dispersion is recorded as solution A. Take 0.2 mmol of pyrrole monomer and precool it in an ice water bath as solution B. Then slowly add solution A to solution B at a drop rate of 0.5 mL / min.
[0062] (5) After the addition of step (4) is completed, place the mixture in a constant temperature water bath at 75°C, stir and evaporate to dryness, collect the resulting powder and transfer it to a tube furnace, and carbonize it in an Ar / H2 atmosphere to obtain a precursor. The carbonization temperature is 900°C, the volume content of H2 in the Ar / H2 mixed gas is 10%, the heating rate is 5°C / min, and the carbonization time is 1.5h;
[0063] (6) The precursor obtained in step (5) is added to a 0.2 mol / L dilute sulfuric acid solution and placed in a constant temperature water bath at 60°C with stirring, acid-washed for 3 h, and centrifuged until the sample supernatant is neutral. The centrifuged substrate is collected and dried in a vacuum drying oven at 60°C for 8 h to obtain a hollow spherical Fe, N co-doped carbon-based high-efficiency zinc-air battery catalyst.
[0064] Example 3
[0065] The preparation method of the hollow spherical Fe, N co-doped porous carbon-based high-efficiency zinc-air battery catalyst of this embodiment comprises the following steps:
[0066] (1) Take 0.3 mL of styrene monomer, extract it with NaOH solution to remove the inhibitor, then add 0.05 g of PVP and 10 mL of deionized water, and pass N2 through the solution for 20 minutes.
[0067] (2) Heat the above solution in a water bath at 60°C for 1 h. Add 0.04 g of potassium persulfate and continue heating and stirring for 20 h.
[0068] (3) After the reaction is completed, filter and dry to obtain powdered PS balls.
[0069] (4) Mix the powdered PS balls obtained in step (3) with metal salts. The masses of iron nitrate, zinc nitrate and PS balls are 0.25 g, 0.08 g and 0.05 g respectively. After stirring and dissolving, ultrasonic dispersion is recorded as solution A. Take 0.25 mmol of pyrrole monomer and precool it in an ice water bath and record it as solution B. Then slowly add solution A to solution B at a drop rate of 0.25 mL / min.
[0070] (5) After the addition of step (4) is completed, place the mixture in a constant temperature water bath at 70°C, stir and evaporate to dryness, collect the resulting powder and transfer it to a tube furnace, and carbonize it in an Ar / H2 atmosphere to obtain a precursor. The carbonization temperature is 950°C, the volume content of H2 in the Ar / H2 mixed gas is 10%, the heating rate is 5°C / min, and the carbonization time is 2 h;
[0071] (6) The precursor obtained in step (5) is added to a 0.3 mol / L dilute sulfuric acid solution and placed in a constant temperature water bath at 70°C with stirring, acid-washed for 2 h, and centrifuged until the sample supernatant is neutral. The centrifuged substrate is collected and dried in a vacuum drying oven at 60°C for 12 h to obtain a hollow spherical Fe, N co-doped carbon-based high-efficiency zinc-air battery catalyst.
[0072] First, the obtained product was characterized by XRD. Figure 1 As shown. In this example, a hollow spherical Fe, N co-doped carbon-based catalyst was successfully prepared, and the (002) crystal plane of graphite carbon and the crystal diffraction peak of metallic iron were visible. Further morphological characterization was performed, and the results were as follows Figure 2 As shown in the figure, it is a hollow sphere with uniform diameter, about 100 to 150 nm. Figure 3 As shown, the N2 adsorption / desorption isotherms are all type IV curves dominated by H3 hysteresis. For the N2 adsorption / desorption isotherms of catalysts such as Fe-N-HPCSs, when the relative pressure (P / P0) is greater than 0.2, an obvious hysteresis loop can be observed, confirming the existence of microporous and mesoporous structures. In order to determine the chemical bonding state of each element in the product, XPS analysis was performed, and the results are shown in Figure 4 As shown. Figure 4 a is the full spectrum of Fe-N-HPCSs. Figure 4 b is its N1s spectrum, from which it can be seen that the existence forms of N element are divided into graphitic nitrogen, pyridinic nitrogen, oxidized nitrogen, and pyrrolic nitrogen, proving the successful doping of N element; Figure 4 c is the high-resolution spectrum of Fe2p, which further confirms the existence of Fe element.
[0073] Example 4
[0074] The preparation method of the hollow spherical Fe, N co-doped porous carbon-based high-efficiency zinc-air battery catalyst of this embodiment comprises the following steps:
[0075] (1) Take 0.2 mL of styrene monomer, extract it with NaOH solution to remove the inhibitor, then add 0.03 g of PVP and 10 mL of deionized water, and pass N2 through the solution for 30 minutes;
[0076] (2) Heat the above solution in a water bath at 65°C for 2 h. Add 0.04 g of potassium persulfate and continue heating and stirring for 6 h.
[0077] (3) After the reaction is completed, filter and dry to obtain powdered PS balls;
[0078] (4) Mix the powdered PS balls obtained in step (3) with metal salts. The masses of iron nitrate, zinc chloride and PS balls are 0.08 g, 0.06 g and 0.02 g respectively. After stirring and dissolving, ultrasonic dispersion is recorded as solution A. Take 0.15 mmol of pyrrole monomer and precool it in an ice water bath and record it as solution B. Then slowly add solution A to solution B at a drop rate of 0.08 mL / min.
[0079] (5) After the addition of step (4) is completed, place the mixture in a constant temperature water bath at 75°C, stir and evaporate to dryness, collect the resulting powder and transfer it to a tube furnace, and carbonize it in an Ar / H2 atmosphere to obtain a precursor. The carbonization temperature is 850°C, the volume content of H2 in the Ar / H2 mixed gas is 8%, the heating rate is 5°C / min, and the carbonization time is 3h;
[0080] (6) The precursor obtained in step (5) is added to a 0.5 mol / L dilute sulfuric acid solution and placed in a constant temperature water bath at 65°C with stirring, acid-washed for 2 h, and centrifuged until the sample supernatant is neutral. The centrifugal substrate is collected and dried in a vacuum drying oven at 60°C for 8 h to obtain a hollow spherical Fe, N co-doped carbon-based high-efficiency zinc-air battery catalyst.
[0081] Example 5
[0082] The preparation method of the hollow spherical Fe, N co-doped porous carbon-based high-efficiency zinc-air battery catalyst of this embodiment comprises the following steps:
[0083] (1) Take 0.25 mL of styrene monomer, extract it with NaOH solution to remove the inhibitor, then add 0.04 g of PVP and 10 mL of deionized water, and pass N2 through the solution for 20 minutes;
[0084] (2) Place the above solution in a water bath and heat it at 65°C for 1.5 h. Then add 0.04 g of potassium persulfate and continue heating and stirring for 8 h.
[0085] (3) After the reaction is completed, filter and dry to obtain powdered PS balls;
[0086] (4) Mix the powdered PS spheres obtained in step (3) with metal salts. The masses of iron sulfate, zinc sulfate and PS spheres are 0.3 g, 0.15 g and 0.04 g respectively. After stirring and dissolving, ultrasonic dispersion is recorded as solution A. Take 1 mmol of pyrrole monomer and precool it in an ice water bath and record it as solution B. Then slowly add solution A to solution B at a drop rate of 0.2 mL / min.
[0087] (5) After the addition of step (4) is completed, place the mixture in a constant temperature water bath at 55°C, stir and evaporate to dryness, collect the resulting powder and transfer it to a tube furnace, and carbonize it in an Ar / H2 atmosphere to obtain a precursor. The carbonization temperature is 700°C, the volume content of H2 in the Ar / H2 mixed gas is 10%, the heating rate is 5°C / min, and the carbonization time is 1h;
[0088] (6) The precursor obtained in step (5) is added to a 0.05 mol / L dilute sulfuric acid solution and placed in a constant temperature water bath at 55°C with stirring, acid-washed for 3 h, centrifuged and washed until the sample supernatant is neutral, then the centrifuged substrate is collected and dried in a vacuum drying oven at 60°C for 8 h to obtain a hollow spherical Fe, N co-doped carbon-based high-efficiency zinc-air battery catalyst.
[0089] Application Example 1
[0090] Electrochemical performance test: 10 mg of the hollow spherical Fe, N co-doped carbon-based catalyst prepared in Example 3 and the commercial Pt / C-20% catalyst were dispersed in 980 μL ethanol and 20 μL Nafion solution (5% wt ) and dispersed and mixed by ultrasonic. Apply 10 μL of the slurry on the rotating disk electrode, wait for it to dry completely, and then measure the linear voltammetric scan (ORR-LSV) curve of the oxygen reduction process on the electrochemical workstation. The ORR-LSV was determined using a saturated Hg / Hg2Cl2 electrode as the reference electrode and a Pt electrode as the counter electrode at a scan rate of 10 mVs -1 The electrolyte was a 0.1 mol / L KOH solution saturated with O2 (before the test, oxygen was introduced at a flow rate of 50 mL / min for about 30 minutes to saturate the solution with oxygen).
[0091] The obtained ORR-LSV curve is as follows: Figure 5 As shown in a, the half-wave potential of the hollow spherical Fe and N co-doped carbon-based catalyst in 0.1 mol / L KOH solution is 0.896 V, showing good electrocatalytic activity and exceeding the performance of other reference catalysts. Specifically, the half-wave potentials of NC, Fe-NC, Fe-N-HPCSs catalysts and commercial Pt-C-20% are 0.664, 0.791 and 0.843 V, respectively. Figure 5 As shown in Figure b, it is a comparison of the half-wave potential Tafel curves of NC, Fe-NC, Fe-N-HPCSs catalysts and commercial Pt-C-20%. It can be seen that Fe-N-HPCSs has the lowest Tafel slope compared with other reference catalysts. Among them, the Tafel slope of Fe-N-HPCSs catalyst is 61.83 mV dec. -1, which is lower than the Tafel slope of Pt / C-20% catalyst (74.89 mV dec -1 ).
[0092] Then, ORR-LSV tests were carried out at different speeds of 0, 400, 600, 900, 1200, 1400, 2000, 2200, and 2400. The results are as follows: Figure 6 As shown in a. As the rotation speed increases, the limiting current density gradually increases.
[0093] The KL equation calculation shows that this electrocatalyst has a 4-electron transfer mechanism ( Figure 6 b) can avoid the formation of destructive H2O2 byproducts, and show high application prospects in zinc-air batteries. The ORR cycle stability test of the catalyst was carried out in an O2-saturated 0.1 mol / L KOH solution, such as Figure 6 As shown in c, after 20 hours of testing, the current density of the catalyst prepared in Example 3 remained at 99.82% of the initial value, which was higher than that of the commercial Pt / C-20% catalyst (86.08%) and had better cycle stability.
[0094] Application Example 2
[0095] Zinc-air battery performance test: The zinc-air battery test device uses a zinc sheet as the anode, 6 mol / L KOH and 0.1 mol / L Zn(Ac)2 solution as the electrolyte, and an air electrode loaded with a catalyst as the cathode. The catalyst is the hollow spherical Fe, N co-doped carbon-based catalyst prepared in Example 3 and the commercial Pt / C-20% catalyst, and the test is carried out under the same conditions. The preparation of the catalyst slurry is the same as that of Experimental Example 4.
[0096] The charge and discharge polarization curves and the corresponding discharge power density curves of the assembled zinc-air battery are shown in Figure 7 As shown in a, the zinc-air battery using the catalyst in Example 3 has an output power of 274.464 mA cm -2 Reaching 164.13 mW cm -2 The peak power density is better than that of commercial Pt / C-20% catalyst (53.94 mW cm -2 , 101.4 mA cm -2 ).
[0097] Figure 7 b is a comparison of the open circuit voltage curves of zinc-air batteries. The open circuit voltage of the battery assembled by hollow spherical Fe and N co-doped carbon-based catalysts is 1.44V, and the open circuit voltage of the battery assembled by commercial Pt / C-20% is 1.37V, indicating that the Fe-N-HPCSs catalyst has better battery performance than the commercial Pt / C-20% catalyst. Figure 7 c, at 5 mA cm -2 At a current density of 1.34 mAhg, the specific capacity of the Fe-N-HPCSs battery is 762.54 mAhg (Zn) -1 , higher than the commercial Pt / C-20% catalyst (760.8 mAhg (Zn) -1 ). Figure 7 d shows that the ZAB based on Fe-N-HPCSs catalyst exhibits a higher discharge platform than the ZAB based on Pt-C-20% catalyst at different discharge current densities. -2 Restore to 1 mAcm -2 When the Fe-N-HPCSs-based ZAB can still recover to 1 mA cm -2 The initial discharge platform of 2.5 nm was obtained, which further confirmed its good stability and rate performance. This may be due to the fact that the construction of the hollow sphere morphology increased the number of exposed active sites, thus showing excellent rate performance.
[0098] For charge and discharge cycle stability test (such as Figure 7 The test current density is 3 mA cm -2 , charging for 300s, discharging for 300s as one cycle, and the test obtained a 370h cycle curve. The corresponding battery charge and discharge potential difference growth value of the electrode loaded with Fe-N-HPCSs catalyst as the positive electrode is 40 mV. The commercial Pt / C-20% catalyst has a large potential difference leap in less than 20h. Therefore, the battery loaded with Fe-N-HPCSs catalyst has a greater advantage in stability.
[0099] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a hollow spherical Fe, N co-doped porous carbon-based catalyst, characterized in that: The following steps are involved: (1) Use NaOH solution to extract and remove the inhibitor in the styrene monomer, and add it together with polyvinyl pyrrolidone into deionized water, stir evenly, and then introduce N2; (2) placing the solution obtained in step (1) in a water bath, heating and stirring, then adding potassium persulfate, and continuing heating and stirring to react; (3) After the reaction in step (2) is completed, filtering and drying are performed to obtain powdered polystyrene spheres; (4) dissolving the powdered polystyrene spheres and metal salt obtained in step (3) in deionized water, stirring and dissolving, and then ultrasonically dispersing the mixture, which is referred to as solution A; precooling the polymer monomer in an ice water bath, which is referred to as solution B; and then slowly dropping solution A into solution B; (5) After the step (4) is completed, the mixture is stirred and evaporated to dryness under water bath conditions, and the resulting powder is collected and carbonized in an Ar / H2 atmosphere to obtain a catalyst precursor; (6) adding the catalyst precursor obtained in step (5) into an acid solution, stirring at a constant temperature, centrifuging and washing until the sample supernatant is neutral, collecting the centrifugal substrate, and drying to obtain a hollow spherical Fe, N co-doped porous carbon-based catalyst; The added amount of the styrene monomer is 0.1-0.9 mL, the added amount of polyvinyl pyrrolidone is 0.01-0.05 g, the volume of deionized water is 1-10 mL, the N2 is introduced for 5-30 minutes, and the added amount of potassium persulfate is 0.02-0.1 g.
2. The method for preparing the hollow spherical Fe, N co-doped porous carbon-based catalyst according to claim 1, characterized in that: In the step (2), the heating temperature is 30-85° C., the heating time is 0.5-3 h, and the continuous heating and stirring reaction time is 6-48 h.
3. The method for preparing the hollow spherical Fe, N co-doped porous carbon-based catalyst according to claim 1, characterized in that: In step (4), the metal salt is a mixture of iron salt and zinc salt, and the mass ratio of iron salt, zinc salt and polystyrene balls is (0.1-0.5):(0.05-0.2):(0.01-0.05), wherein the iron salt is ferric sulfate, ferric nitrate or ferric chloride, and the zinc salt is zinc sulfate, zinc nitrate or zinc chloride.
4. The method for preparing the hollow spherical Fe, N co-doped porous carbon-based catalyst according to claim 1, characterized in that: In step (4), the polymer monomer is any one of pyrrole, aniline or thiophene, and Fe 3+ The molar ratio to the polymer monomer is 1:(0.2~2), and the droplet acceleration rate is 0.05~0.5 mL / min.
5. The method for preparing the hollow spherical Fe, N co-doped porous carbon-based catalyst according to claim 1, characterized in that: The temperature for stirring and evaporating to dryness in step (5) is 35-85°C.
6. The method for preparing the hollow spherical Fe, N co-doped porous carbon-based catalyst according to claim 1, characterized in that: In the step (5), the volume content of H2 in the Ar / H2 mixed gas is 5%-10%, the carbonization temperature is 700-950°C, the carbonization time is 1-3h, and the heating rate is 3-15°C / min.
7. The method for preparing the hollow spherical Fe, N co-doped porous carbon-based catalyst according to claim 5, characterized in that: In the step (6), the acid solution is a 0.05-2 mol / L dilute sulfuric acid solution, the pickling time is 1-3 h, the stirring temperature is 40-70° C., the drying temperature is 60° C., and the drying time is 8-12 h.
8. The hollow spherical Fe, N co-doped porous carbon-based catalyst prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The bimetallic chelating polymer obtained by in-situ oxidative polymerization is uniformly coated on the surface of polystyrene.
9. Use of the hollow spherical Fe and N co-doped porous carbon-based catalyst according to claim 8 in zinc-air batteries.
